Distinct axial and lateral interactions within homologous filaments dictate the signaling specificity and order of the AIM2-ASC inflammasome - Mariusz Matyszewski (Nature Portfolio, 2021)
AIM2-ASC inflammasomes are filamentous signalling platforms that play a central role in host innate defence. Here, the authors present the filament cryo-EM structure of the inflammasome receptor AIM2, which is very similar to the adaptor ASC filament structure. By employing Rosetta and Molecular Dynamics simulations the authors provide further insights into the directionality and recognition mechanisms of the individual AIM2 and ASC filaments, which is further validated with biochemical and cellular experiments.